Manager Of Instagram As A Means Of Information In National Union And North Jakarta Administrative City Politics - Widyastuti, Ayu; Chandra Agustin, Dinar Ayu (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The development of information technology brings a change in society. The birth of social media makes people's behavior patterns experience a shift in culture, ethics and existing norms. Indonesia with a large population with various ethnic, racial and religious cultures has a lot of potential for social change. From various backgrounds and ages, almost all Indonesian people own and use social media as a means of obtaining and conveying information to the public. Social media will be more effective and time efficient. The public who have followed Instagram can see uploaded photos of internal and external events that took place at the National Unity and Politics of the Administrative City of. The development of information facilities has made the government also use social media as a means of conveying information in this Digital Age. The Instagram site is an alternative means of conveying public information. This information quickly spread widely among the public, one of which was because of the role of social media, both Instagram and Facebook. Social media is an alternative for conveying information because many Indonesian people use social media, so that information can be obtained easily and quickly As for the research method used in this study using descriptive qualitative which explains as the breakdown of problems or events that have been raised in this study, this researcher does not explain or find out between the relationships that will test the hypothesis.